(untitled) (REMUNOM, 2025)
The teaching of Hydrostatics, a branch of Physics that studies fluids at rest, often presents challenges due to the abstract nature of concepts such as density, pressure, and buoyancy. This work presents the development of a 2D educational digital game, created using Godot Engine 4.0, with the purpose of making these concepts easier to understand in a playful and interactive way. The game integrates mechanisms that simulate hydrostatic principles such as density variation, pressure effects, and buoyant force combined with open-source visual and sound resources. Playtests were conducted with 30 participants of different age groups, along with evaluative questionnaires. Results showed a high level of rule clarity (97% approval), strong satisfaction (average score of 9.78), and higher engagement among younger players, confirming the pedagogical potential of the tool. It is concluded that digital games, when properly designed, represent effective alternatives to traditional teaching, fostering greater motivation, active participation, and meaningful learning in Physics education.